Extraction Selectivity of a Quaternary Alkylammonium Salt for Trivalent Actinides over Trivalent Lanthanides: Does Extractant Aggregation Play a Role?. Issue 4 (7th June 2017) - Knight, Andrew W.; Chiarizia, Renato; Soderholm, L.
ABSTRACT: The extraction behavior of a quaternary alkylammonium salt extractant was investigated for its selectivity for trivalent actinides over trivalent lanthanides in nitrate and thiocyanate media. The selectivity was evaluated by solvent extraction experiments through radiochemical analysis of 241 Am and 152/154 Eu. Solvent extraction distribution and slope-analysis experiments were performed with americium(III) and europium(III) with respect to the ligand (nitrate and thiocyanate), extractant, and metal (europium only) concentrations. Further evaluation of the equilibrium expression that governs the extraction process indicated the appropriate use of the saturation method for estimation of the aggregation state of quaternary ammonium extractants in the organic phase. From the saturation method, we observed an average aggregation number of 5.4 ± 0.8 and 8.5 ± 0.9 monomers/aggregate for nitrate and thiocyanate, respectively. Through a side-by-side comparison of the nitrate and thiocyanate forms, we discuss the potential role of the aggregation in the increased selectivity for trivalent actinides over trivalent lanthanides in thiocyanate media.